In House Training Pencegahan dan Pengendalian Infeksi (PPI) Pada Tenaga Kesehatan di RS AMC Yogyakarta - Maria Ulfa; Rizky Firdaus; Novada Indra Roesdiana; Nurhidayati; Niken Andriani; Purwanto (The Journal Publishing, 2022)
The hospital as a health facility that provides health services to the community has a very important role in improving the health status of the community. For the implementation of infection in hospitals and other health care facilities, it is necessary to implement Infection Prevention and Control (PPI), activities that include planning, coaching, education, and training, as well as monitoring and evaluation. from this service activity, PPI training participants understand and practice Infection Prevention and Control at AMC Hospital Yogyakarta. Community service activities at AMC Hospital Yogyakarta are planned to use the action research method. Overall there was an increase in participants' knowledge which could be seen from the correct explanation before and before the training was held. Results Based on the service activities that have been carried out, it is necessary to follow up on improving infection prevention and control at home by conducting training that include all hospital employees